ChemInform Abstract: Schisphenlignans A—E: Five New Dibenzocyclooctadiene Lignans from Schisandra sphenanthera. Issue 26 (6th June 2013) - Sun, Han‐Dong; et al., et al.
Abstract isolation, structure and insulin sensitivity activity